Różne aspekty ograniczenia wydajności pompy wyporowej o stałej objętości jednostkowej - Pawelski, Zbigniew; Gauthier, Pierre; Werner, Andrzej; Goszczak, Jarosław (Wydawnictwo Politechniki Łódzkiej, 2015)
A solution has been proposed that ensures oil drain from the discharge chamber to the pump inlet. The piston of a relief valve is controlled by a differential pressure resulting from Bernouilli effect. The start value of oil draining is to be controlled by the spring initial deflection and modification of the flow section in the outlet channel of the pump. By diminishing the spring force, 30% reduction of the flow rate has been achieved. It is difficult to get more because of stability reasons. A more effective method is to decrease the local flow section where a static pressure probe is placed. This way 36% reduction has been achieved and there is no reason to not to go further.
Artykuł zamieszczony w : „Problemy rozwoju maszyn roboczych” XXVIII Konferencja Naukowa Zakopane 2015 (Materiały konferencyjne wydane w serii Monografie PŁ)